2017
DOI: 10.1080/19425120.2016.1249579
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern, Age, and Growth of Blue Sharks in the South Atlantic Ocean

Abstract: The distribution pattern and the age and growth of Blue Sharks Prionace glauca were described based on 44,092 and 785 specimens, respectively, that were collected by scientific observers onboard Taiwanese longline fleets in the South Atlantic Ocean between December 2004 and December 2013. Size segregation was found, and the mean length of Blue Sharks was significantly larger in the equatorial–tropical area (0–15°S) than in the subtropical–temperate area (south of 15°S) during all seasons. Males predominated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…Growth parameters we report for this study differ from those reported for sharks in the eastern North Pacific Ocean (Cailliet and Bedford, 1983;Blanco-Parra et al, 2008), possibly because few larger and older specimens (most individuals were less than 200 cm PCL) were represented in samples in those studies. The size range of specimens reported from the central South Pacific Ocean by Joung et al (2017) is similar to the range we report, as are estimates of growth parameters, especially asymptotic length (Table 5). However, our estimated female as- Table 4 Estimates, with 95% confidence intervals (95% CIs), of the parameters for the von Bertalanffy growth model used to examine differences in growth parameters between sexes for blue sharks (Prionace glauca) in the western North Pacific Ocean.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Growth parameters we report for this study differ from those reported for sharks in the eastern North Pacific Ocean (Cailliet and Bedford, 1983;Blanco-Parra et al, 2008), possibly because few larger and older specimens (most individuals were less than 200 cm PCL) were represented in samples in those studies. The size range of specimens reported from the central South Pacific Ocean by Joung et al (2017) is similar to the range we report, as are estimates of growth parameters, especially asymptotic length (Table 5). However, our estimated female as- Table 4 Estimates, with 95% confidence intervals (95% CIs), of the parameters for the von Bertalanffy growth model used to examine differences in growth parameters between sexes for blue sharks (Prionace glauca) in the western North Pacific Ocean.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, because we used the thin-sectioning method on older sharks, we minimized underestimation of age. The aging precision (IAPE and CV) that we achieved by combining techniques is comparable to that from the use of a single technique like thin sectioning (Lessa et al, 2004), silver nitrate impregnation (Blanco-Parra et al, 2008), or X-ray imaging (Joung et al, 2017;Joung et al, 2018). Consequently, our aging Table 5 Estimates of growth parameters of the von Bertalanffy growth function for blue sharks (Prionace glauca) from previous studies.…”
mentioning
confidence: 67%
“…Also, those values for younger and smaller specimens (<200 cm PCL) were lowest in the burn method (3.0% and 4.2%), whereas those for older specimens were lowest in the unstained shadowing method (7.6% and 10.7%). The IAPE values for blue shark in other studies were 3.0% (silver nitrate [whole centra]: Blanco‐Parra, Galvan‐Magnna, & Marquez‐Farias, ), 7.9% (unstained whole centra: Jolly et al., ), and 3.8% and 9.0% (X‐ray [whole centra]: Joung, Lyu, Su, Hsu, & Liu, ; X‐ray [thin section]: Manning & Francis, ). Similarly, the CVs for blue shark in other studies were 5.0% and 12.8% (X‐ray [whole centra]: Joung et al., ; X‐ray [thin section]: Manning & Francis, ) and 15.0% (unstained thin section: Skomal & Natanson, ).…”
Section: Discussionmentioning
confidence: 89%
“…Also, those values for younger and smaller specimens (<200 cm PCL) were lowest in the burn method (3.0% and 4.2%), whereas those for older specimens were lowest in the unstained shadowing method (7.6% and 10.7%). The IAPE values for blue shark in other studies were Similarly, the CVs for blue shark in other studies were 5.0% and 12.8% (X-ray [whole centra]: Joung et al, 2017; X-ray [thin section]: Manning & Francis, 2005) and 15.0% (unstained thin section: Skomal & Natanson, 2003). The IAPE and CV reference values have been reported to be 5.5% and 7.6%, respectively (Campana, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the Atlantic Ocean, the reproductive biology of blue shark has also been reported (Castro & Mejuto, 1995;Hazin et al, 2008;Kouamé et al, 2019;Pratt, 1979). Similarly, Joung et al (2005Joung et al ( , 2017 analysed the shark by-catch of the Taiwanese tuna longline fishery in the South Atlantic; Carvalho et al (2015) reported fishery selectivity for blue sharks in the South Atlantic based on satellite tagging; Coelho et al (2015Coelho et al ( , 2017 described the size, sex ratio and distribution pattern of blue sharks in the Atlantic and Indian Oceans based on observer data from major fishing fleets. Nonetheless, key reproductive parameters such as length at maturity and litter size of the blue shark were found to vary among different regions (Nakano & Stevens, 2008;Pratt, 1979).…”
Section: Introductionmentioning
confidence: 99%